2018
DOI: 10.5455/handmicrosurg.271907
|View full text |Cite
|
Sign up to set email alerts
|

Posterior interosseous nerve palsy caused by a parosteal lipoma seated over the proximal radius; a case report and review of the literature

Abstract: Several different pathologies may play a role in the etiology of posterior interosseous nerve (PIN) palsy such as trauma, radial tunnel syndrome, tumors, vasculitis, septic arthritis, and rheumatoid synovitis. The most common atraumatic factor is the compression of the nerve through its anatomic path. Parosteal lipoma around the proximal radius is the leading solid tumor seen among the neoplastic lesions. Although it is common, there are only case reports or few case series reported in the current literature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Even though MRI is the imaging modality of choice for these conditions, skiagrams may reveal a soft tissue radiolucent area consistent with a lipoma. 6,7 In our case plain radiographs were found to be normal.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Even though MRI is the imaging modality of choice for these conditions, skiagrams may reveal a soft tissue radiolucent area consistent with a lipoma. 6,7 In our case plain radiographs were found to be normal.…”
Section: Discussionsupporting
confidence: 48%
“…Some studies have advocated use of anterior approach for excision of these lipomas. 7,8 However, we didn't find any difficulty using posterior approach. Regardless of the incision and approach, the aim of the surgery should be meticulous en bloc excision of the mass without causing iatrogenic damage to PIN.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is an agreement among surgeons that the recovery of the nerve function depends mainly on the duration of symptoms, and early surgical decompression will offer faster recovery and better functional outcomes [1,9]. However, despite the success of lesion surgical excision to provide PIN full recovery, in some cases, even with early surgical intervention, full recovery was not gained, requiring further tendon transfer [10]. Vikas et al suggested that surgical decompression delay beyond 18 months may lead to fibrosis of the muscles innervated by the PIN, increasing the chance for further tendon transfer to gain accepted functional outcomes [1].…”
Section: Discussionmentioning
confidence: 99%
“…The approach used for surgery should offer a wide exposure and a safe window to perform dissection and excision of the mass for the safety of the neural structures. We used the anterior approach for excising the mass, which was recommended in previous studies, as it offered better visualization and access to the lesion, and better use of the anterior approach for excising these lesions [5,8,10]. However, in their case report, Vikas et al used the posterior approach to access a parosteal bilobed lipoma, and they reported excellent visualization of PIN and its branches, which guarded against iatrogenic injury nerve during dissecting and excising the lesion [1].…”
Section: Discussionmentioning
confidence: 99%